Revisiting an old antibiotic: bacitracin neutralizes binary bacterial toxins and protects cells from intoxication. Issue 4 (30th January 2019) - Schnell, Leonie; Felix, Ina; Müller, Bastian; Sadi, Mirko; von Bank, Franziska; Papatheodorou, Panagiotis; Popoff, Michel R.; Aktories, Klaus; Waltenberger, Eva; Benz, Roland; Weichbrodt, Conrad; Fauler, Michael; et al.
ABSTRACT: The antibiotic bacitracin (Bac) inhibits cell wall synthesis of gram‐positive bacteria. Here, we discovered a totally different activity of Bac: the neutralization of bacterial exotoxins. Bac prevented intoxication of mammalian cells with the binary enterotoxins Clostridium botulinum C2, C . perfringens ɩ, C. difficile transferase (CDT), and Bacillus anihracis lethal toxin. The transport (B) subunits of these toxins deliver their respective enzyme (A) subunits into cells. Following endocytosis, the B subunits form pores in membranes of endosomes, which mediate translocation of the A subunits into the cytosol. Bac inhibited formation of such B pores in lipid bilayers in vitro and in living cells, thereby preventing translocation of the A subunit into the cytosol. Bac preserved the epithelial integrity of toxin‐treated CaCo‐2 monolayers, a model for the human gut epithelium. In conclusion, Bac should be discussed as a therapeutic option against infections with medically relevant toxin‐producing bacteria, including C . difficile and B. anthracis, because it inhibits bacterial growth and neutralizes the secreted toxins.—Schnell, L., Felix, I., Müller, B., Sadi, M., von Bank, F., Papatheodorou, P., Popoff, M. R., Aktories, K., Waltenberger, E., Benz, R., Weichbrodt, C., Fauler, M., Frick, M., Barth, H. Revisiting an old antibiotic: bacitracin neutralizes binary bacterial toxins and protects cells from intoxication. FASEB J. 33, 5755–5771 (2019). www.fasebj.org